MUSLIMANSKA ODJEĆA U EVROPI: DEBATE O MAHRAMI (2) - Shadid, W.; Van Koningsveld, P. S.; Karčić, Hamida (Novi Muallim, 2007)
Izvor: Journal of Islamic Studies (Oxford Universiry Press), vol. 16, no. 1. januar 2005. str. 35-61 Prijevod: Hamida Karčić